Symbolic Acts of Jesus - Wojciechowski, Michał (Studia Warmińskie, 2014)
Symbolic acts of Jesus could be seen as a neutral sample of the traditions about his life. Their study is relatively free of presuppositions, because this category has not been involved in doctrinal discussions. It was neither important for the theological concepts of the biblical authors, nor for the hermeneutical theories of modern scholars. In the examples discussed in this paper (Mk 2:15-17; 1:40-45; 10:13-14,16; 11:1-11; 11:12-14; 11:15-19; 14:25; 15:23; Jn 13:1-20; 20:22; laying on hands, touching, spitting) historical kernels can be identified. It confirms that in the Gospel we can find many reliable traditions about historical Jesus and even about his intentions.